NMDA receptor modulation by Esculetin: Investigating behavioral, biochemical and neurochemical effects in schizophrenic mice model - Iqra Khalid; Uzma Saleem; Bashir Ahmad; Mohammed F. Hawwal; Ramzi A. Mothana (Saudi Pharmaceutical Journal, 2024)
Schizophrenia, a global mental health disorder affecting approximately 1 % of the population, is characterized by neurotransmitter dysregulation, particularly dopamine, serotonin, and glutamate. Current antipsychotic therapies, despite their efficacy, are accompanied by adverse effects, which has motivated researchers to investigate more secure substitutes. This study examines the potential antipsychotic effects of esculetin, a natural coumarin derivative recognized for its wide-ranging pharmacological activities (anti-inflammatory, antioxidant, anti-pathogenic, anticancer, and neuroprotective), in animal model of schizophrenia induced by ketamine. In order to induce disease, acute and chronic ketamine administration was performed on Swiss albino mice, supplemented with esculetin (as the test substance) and clozapine (as the reference standard). Behavioral studies and biochemical assays were performed to evaluate positive, negative, and cognitive symptoms of schizophrenia, as well as antioxidant and oxidant levels in various brain regions. Esculetin demonstrated significant improvements in behavioral symptoms, attenuated oxidative stress and neuroinflammation, and modulated neurotransmitter levels. Afterwards, ELISA was performed to evaluate levels of schizophrenia biomarkers AChE, BDNF. Moreover, proinflammatory cytokines (IL-6 and TNF-α) and NF-κB were also determined. Histopathological parameters of under study brain parts i.e., hippocampus, cortex and striata were also assessed. Esculetin and clozapine significantly (***p < 0.0001) altered ketamine induced behavioral symptoms and attenuated ketamine induced oxidative stress and neuroinflammation. Additionally, esculetin significantly (***p < 0.0001) altered neurotransmitter (dopamine, serotonin, glutamate) levels. ELISA analysis depicts ketamine reduced BDNF levels in hippocampus, cortex and striata while esculetin significantly (***p < 0.0001) increased BDNF levels in under study three parts of brain. Histopathological changes were seen in test groups. The findings of this study indicate that esculetin may have therapeutic potential in the treatment of schizophrenia induced by ketamine. As a result, esculetin may have the potential to be utilized as a treatment for schizophrenia.